2018
DOI: 10.1016/j.bjpt.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of postural control and maturation of sensory systems in children of different ages a cross-sectional study

Abstract: HighlightsThis study has promotes a better understanding on the evolution of stability, functional maturation of sensorial integration and postural adjustments in children.This study has combined biomechanical and motor control concepts, discussing the parameters separately stability and postural adjustments.This study indicated Postural stability and adjustments were associated with age and were influenced by sensory manipulation and seven-year-olds seem to go through a period of differentiated singularity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 27 publications
1
31
0
2
Order By: Relevance
“…Similar data were obtained for children of 3-11 years (n = 1181); the authors found that the rate of decrease in sway area and velocity gradually slowed down by the age of 10-11 [9,31]. The age-related increase in VCP and AS was probably associated with the maturation of the key components of the postural system (sensory, muscular, and central nervous systems [32][33][34]) and a better posture regulation due to a gradual shift of the COP from the heels forward, to the toes, with age [9,31]. It was shown that a functionally mature central nervous system fully integrates sensory information in order to optimize postural control.…”
Section: Age-related Differences In Postural Stability In Athletessupporting
confidence: 66%
See 2 more Smart Citations
“…Similar data were obtained for children of 3-11 years (n = 1181); the authors found that the rate of decrease in sway area and velocity gradually slowed down by the age of 10-11 [9,31]. The age-related increase in VCP and AS was probably associated with the maturation of the key components of the postural system (sensory, muscular, and central nervous systems [32][33][34]) and a better posture regulation due to a gradual shift of the COP from the heels forward, to the toes, with age [9,31]. It was shown that a functionally mature central nervous system fully integrates sensory information in order to optimize postural control.…”
Section: Age-related Differences In Postural Stability In Athletessupporting
confidence: 66%
“…It was shown that a functionally mature central nervous system fully integrates sensory information in order to optimize postural control. Normally, the CNS fully develops by the age of 9: the first to mature are sensory regions responsible for the use of visual information, followed by those responsible for proprioceptive information and then, finally, those responsible for the integration of vestibular information [34]. According to our data, postural stability increases, even until an older age of 18-30 years.…”
Section: Age-related Differences In Postural Stability In Athletesmentioning
confidence: 51%
See 1 more Smart Citation
“…By 6 years of age, though, children have achieved adult levels in some specific aspects of postural control [9, 13, 14]. The biggest developmental changes regarding balance control occur in children aged 6–8 [15, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…There are also papers arguing that the locomotor and postural model in 7-year-olds is similar to adults [15][16][17]. Nevertheless, with new experiences and skills, it is possible to continue the development of all elements engaged in postural control, and keeping correct posture in children up to the age of 12 can be harder than in adults due to lacking integration of signals coming from different receptors [18,19]. In our study, we did not observe any correlation between age and anthropometric parameters.…”
Section: Discussionmentioning
confidence: 99%